Aspects of Shaybani's doctrine on earning a living : annotated translation on selection from kitab al-Kasb - Abubakar, Isma'il Ya'u (International Institute of Islamic Thought and Civilization, International Islamic University Malaysia, 2009)
This dissertation presents an annotated English translation of selected parts of Kitab al-kasb - a famous piece of classical al-Kasb literature composed by Mu.J;iammd b. alHasan al-ShaybanI (d.804 CE). It covers a wide array of issues concerning the earning of significant livelihood. Amongst the most notable ones are obligation of types of earning, rules and etiquettes to be followed in economic pursuits, avoidance of extravagance in spending, virtues of wealth and vices of poverty. While al-ShaybanI persistently underscores the indispensability of earning and illustrates thankfulness for wealth to patience in poverty, he does not neglect the overriding necessity of restraining and guiding economic pursuits with moral-ethical-spiritual bridles. Exploration of this balancing attitude of al-ShaybanI is the main subject of this present study. In the context of contemporary endeavour by economically- challenged Muslim nations and individuals, discovering this balance may provide economic advancement.